Evaluating intergenerational risks: Probabillity adjusted rank-discounted utilitarianism - Geir B. Asheim; Stéphane Zuber (University of Oslo, Department of Economics, 2015)
Climate policies have stochastic consequences that involve a great number of generations. This calls for evaluating social risk (what kind of societies will future people be born into) rather than individual risk (what will happen to people during their own lifetimes). As a response we propose and axiomatize probability adjusted rank-discounted critical-level generalized utilitarianism (PARDCLU), through a key axiom that requires that the social welfare order both be ethical and satisfy first-order stochastic dominance. PARDCLU is useful for evaluating intergenerational risks, is ethical in contrast to discounted utilitarianism, and avoids objections that have been raised against other ethical criteria. PARDCLU is shown to handle situations with positive probability of human extinction, and is linked to decision theory by yielding rank-dependent expected utilitarianism - but with additional structure - in a special case.
Keywords: D63; D71; D81; H43; Q54; Q56; 330; social evaluation; population ethics; decision-making under risk; critical-level utilitarianism; social discounting